What is the underlined word ??
Answer:-1
Step-by-step explanation:
I rewrote it so it looks like this:
6y+6(1+3y)=-18
6y+6(1)+6(3y)=-18
6y+6+18y=-18
24y+6=-18
<u> -6 -6</u>
<u>24y</u>=<u>-24</u>
24 24
y=-1
Answer:
D.
Step-by-step explanation:
-2*-3=6 -2*5=-10. -2*1=-2
-2*8=-16. -2*-2=4. -2*3=-6
-2*2=-4. -2*1=-2. -2*-4=8
The point slope form of the line has the following form:
y – y1 = m (x – x1)
The slope m can be calculated using the formula:
m = (y2 – y1) / (x2 – x1)
m = (3 - 0) / (0 – 4) = - ¾
So the whole equation is:
y – 0 = - ¾ (x – 4)
y = - ¾ (x – 4) or
<span>y = - 0.75 (x – 4)</span>